O sofrimento psíquico de estudantes da pós-graduação stricto sensu em Psicologia: reflexões a partir da Teoria da Atividade de A. N. Leontiev e da Patopsicologia de B. V. Zeirgarnik - BEATRIZ MARQUES CARVALHO (2023)
The recent budget cuts made on Brazilian Education, based on a neoliberal policy, with an evident conservative ideology, reflect on the study and research conditions of graduate students in Brazil. Furthermore, productivity demands, the bureaucratization of university relations of study and work, among others, are factors that may be linked to psychological distress in the process of training new researchers and professors in the country. There is still little research focused on the illness of graduate students, which demands from Psychology an understanding of this fact. The present research has the general objective of investigating the factors that permeate the psychic suffering of stricto sensu graduate students in Psychology. The study is based on Historical-Cultural Psychology., taking as reference the Activity Theory of A. N. Leontiev and the Experimental Pathopsychology of B. V. Zeigarnik. The methodology used is bibliographic research and field research. This was carried out through the application of questionnaires in Higher Education Institutions in the Midwest region of Brazil. In the first chapter, we present a literature review, which points to an insufficient number of researches on the illness or psychic suffering of postgraduate students in Brazil and that the published researches, for the most part, do not explain the theoretical basis of the work. In the second chapter, the theoretical foundation of the present dissertation is presented, focusing on Leontiev's Activity Theory and Zeigarnik's Experimental Pathopsychology, mainly on their contributions to the investigation of human suffering. In the third and last chapter, the field research data are presented. The analysis carried out below is based on the Activity Theory and experimental Pathopsychology. The study included 46 graduate students from stricto sensu Graduate Programs in Psychology in the states of Mato Grosso, Mato Grosso do Sul and the Federal District. The results obtained show the overload assumed by graduate students, involved in completing graduate studies and working to guarantee their livelihood, added to the demands of domestic life and, in some cases, motherhood. Bureaucratization and external factors that delay the completion of Postgraduate activities and the distanced relationship between advisee-advisor are configured as factors that contribute to the process of suffering. In addition, the context of the pandemic and social isolation contributed to the reduction of the support network of Graduate Students and the impoverishment of experiences during training. Such suffering is expressed as anxiety, anguish, feelings of inadequacy and depressive symptoms. Despite the difficulties and suffering experienced, we observed resistance and restructuring of links between the higher psychological functions to survive and respond to the demands posed by the activity in question. It is necessary, even so, for changes in Brazilian policy regarding Education and also in Graduate Studies so that this activity resumes its role as a promoter of the humanization process. With this study, we intend to highlight, through the intertwining between A. N. Leontiev's Activity Theory and B. V. Zeigarnik's Experimental Pathopsychology, the main determinations about the suffering of graduate students, which permeate the training process, and present subsidies so that Graduate Programs in Psychology can conduct activities working towards the mental health of students.